The Administration of Relief to the Unemployed in Vancouver during the Great Depression - Belshaw, John Douglas (Simon Fraser University, 1984)
Unemployment in Vancouver, Canada, during the Great Depression posed a significant threat' to the continuation of political and social norm. The emergence of a large body of workers without jobs, many of whom could vote at the civic level, demanded the attention and intervention of private and government agencies. The response of the City of Varcouver and two major Christian denominations to the unemployment crisis is the subject of this thesis, The documentary evidence utilized came mainly from collections at the Vancouver School of Theology, the Catholic Charities and the City of Vancouver Archives. The inadequacy and abuse of contemporary statistical resources perpetuated a view of the unemployed that emphasizod their potential for social disruption. Despite the fact that most of Vancouver's jobless citizens were permanent residents, community leaders and rglief planners took their cues from the single unemployed transients, a group that was pore likely to derail revolutionary ideas with an extension of its limited relief programmes, However, both church and state were constrained by the shortage of money. Consequently, in the absence of a strong social work ideology, relief was more a reflection of political and fiscal considerations than of the shifting needs of the unemployed. Relief was, simply put, the least expensive means of reintegrating the dispossessed into the established social milieu.
OCLC: 15937891
Keywords: Academic Dissertation; Academic theses; Aide sociale Colombie-Britannique Vancouver; British Columbia Vancouver; Church work with the unemployed; Church work with the unemployed British Columbia Vancouver; Chômeurs Services Colombie-Britannique Vancouver; Public welfare; Public welfare British Columbia Vancouver; Social conditions; Social policy; Thèses et écrits académiques; Unemployed Services for; Unemployed Services for British Columbia Vancouver; Vancouver (B.C.) Social conditions; Vancouver (B.C.) Social policy